Phylogenetic analyses of the subfamily Scarabaeinae (Coleoptera: Scarabaeidae) provide new insights into the Mexican Transition Zone theory - Moctezuma, Victor; Monteros, Alejandro Espinosa De Los; Halffter, Gonzalo (Zootaxa, 2024)
Being areas of biotic overlap located between biogeographic regions, transition zones function as natural laboratories. The present study explores the phylogenetic history of the dung beetle subfamily Scarabaeinae, in order to present an evolutionary scenario that allows inference of the biogeographic history of the Mexican Transition Zone (MTZ) and integration of the distributional patterns of its biota. The species sampling included 94 New World taxa (93 species of Scarabaeinae and one species of Aphodiinae). The phylogenetic relationships of the main clades recovered in our study were supported with PP values ≥ 0.95. Based on the BAYAREALIKE model to reconstruct the ancestral distributional patterns of Scarabaeinae, we inferred a complex scenario with 19 dispersal events, 15 vicariance events, and three extinctions. We suggest that the Ancient Neotropical and Tropical Paleoamerican patterns represent the most likely ancestral distributional patterns for the Scarabaeinae of the MTZ, which probably settle there during the Eocene-Oligocene. The rest of the Scarabaeinae distributional patterns were assembled in subsequent periods. The results suggest that the MTZ had two separate formation stages: a Paleo-MTZ (Eocene-Miocene) and a current MTZ (Pliocene-Anthropocene). We conclude that the evolutionary history as well as the dispersal-vicariance scenario for the Scarabaeinae of the MTZ fits the “out of the tropics” model.